RANCANG BANGUN ALAT PENYIRAMAN TANAMAN OTOMATIS MENGGUNAKAN METODE FUZZY BERBASIS ARDUINO DI TAMAN PERUMAHAN GADING JUNTI ASRI - Alvin Nurrochman; Rohmat Nur Ibrahim; Cahyo Hermanto (Jurnal Computech & Bisnis (e-Journal), 2022)
he design of the Automatic Plant Watering Prototype is something that can provide benefits to the process of watering existing plants in a garden or park that is in a housing or location that has a garden, how the automatic plant watering process can run smoothly in accordance with established procedures and run according to the needs of the plant. In the face of today's modern era, farmers or park rangers need a system to improve performance in plant care and the quality of plant management and the watering and fertilizing processes that run in it, otherwise it will hamper the performance of the farmers themselves. Gading Junti Asri Housing is no exception, namely housing that always greens its environment, has problems that often occur because there is no system to water plants automatically, garden guards often forget to water plants because there is no automatic plant watering system. Design of an automatic plant watering prototype This has the advantage of automatically watering the plants. When the soil is dry, it can detect soil moisture in the plants. Automatic watering is installed, using the fuzzy method to make it easier to process data from days 1-7 to help analyze plants. Keywords : Planning, Wattering, Fuzzy logic